HIF‐1α‐mediated BMP6 down‐regulation leads to hyperproliferation and abnormal differentiation of keratinocytes in vitro. Issue 11 (9th October 2018) - Kim, Jin Hee; Bae, Hyun Cheol; Kim, Jaehyung; Lee, Hana; Ryu, Woo‐In; Son, Eui Dong; Lee, Tae Ryong; Jeong, Sang Hoon; Son, Sang Wook
Abstract: Hypoxia‐inducible factor‐1α (HIF‐1α) has been reported to be up‐regulated in psoriatic epidermis, resulting in increased proliferation and abnormal differentiation of human keratinocytes (KCs). However, the role of HIF‐1α in psoriatic epidermis, which is mainly composed of KCs, is poorly understood. Here, we show that morphogenic protein 6 (BMP6) is down‐regulated when HIF‐1α is upregulated in patients with psoriasis skin lesions. HIF‐1α overexpression in primary human KCs promoted proliferation and inhibited terminal differentiation. Furthermore, HIF1‐α repressed the expression of BMP6 by binding directly to the hypoxia‐response element (HRE) in the BMP6 promotor region, which shows that BMP6 is a novel target gene of HIF‐1α. We also found that HIF‐1α‐mediated BMP6 suppression could alter the proliferation status by modulating the expression levels of cell cycle regulatory proteins and also affect the early differentiation of KCs. Therefore, we suggest that HIF‐1α‐dependent BMP6 suppression has a critical role in the induction of hyper‐proliferation and abnormal differentiation in psoriatic KCs.